PENGEMBANGAN MEDIA PEMBELAJARAN MATERI BANGUN RUANG SISI DATAR BERBASIS APLIKASI HOLOGRAM UNTUK PESERTA DIDIK KELAS VIII SMP - GITA ANGGRAINI (Departemen Matematika, 2021)
Mathematics is one of the subjects that can help students to think logically, analyze, critically, and the ability to work together. However, the mathematics achievement of students is still low, based on the results of the National Examination in 2019, at the Junior High School level especially on geometry content with an average value of 42,16. This is because the use of learning media is still focused on textbooks so that it does not support the learning process. The Hologram application is a learning media on the learning content of flat side space. This application is designed with three-dimensional object modeling, animation and audio explanations. In addition, there is interaction with users in terms of finding formulas so that the learning process more better. This research uses a modified Plomp model consisting of a priliminary research stage and a prototyping phase. The validity value based on content experts and media experts is 97,927 and 90,278. These results indicate that the media is very valid. The practicality value based on ease of use, suitability for time and attractiveness is 92,59; 95,83 and 92,71. These results indicate that the media is suitable to use as a learning media. Keywords—Geometry, Hologram Application, Learning Media